A legal study on the effectiveness of the Election Offences Act 1954 ('ACT 5') To regulate election expenses in Malaysia / Mohd Azmi Kassim - Kassim, Mohd Azmi (2017)
This research covers the topic on the effectiveness of the Election Offences Act 1954 ('Act 5') in regulating election expenses in Malaysia. The principal reason for embarking on this research is the profound concern on election expenses which have significant bearing on the integrity of elections and democracy as well as governance in the country. In this regard, the election expenses are being paid by the election candidates themselves and/or their political parties. The massive amount of money expended (known as 'money polities') may be used to shape the electoral outcome. When this occurs, capable candidates may be defeated by undeserving candidates who are financially superior. The latter candidates after being elected may then direct their energy in recouping the amount they had spent. It can therefore be expected that there could be abuse of power by them. If so, this would dangerously threaten the fabric of democracy and governance. There would be consequently less time spent to devote on economic development and welfare. Thus, ultimately the people suffer. The election expenses are inextricably linked to party funding. The logic is simply that having better funding would enable candidates to spend more in their campaign expenditure. Thus, nothing would stop them from utilizing their financial resources to influence voters to win. Hence, in order to minimize the abuse of power and corruption, there is a serious need to exert some control on party funding. In this respect, it should be mindful that donors are not purely altruistic and have vested interest when contributing to party funding. The 'pay time' will come after the election. The issues of election expenses and funding are prevalent in other countries too. Accordingly, this research would also focus on the electoral laws of United Kingdom, Australia and Singapore which comprised the Commonwealth countries. The input received therefrom could be used to reform and strengthen our electoral laws which would hopefully, result in clean and fair elections.